A Systematic Review of Effects of Waterpipe Smoking on Cardiovascular and Respiratory Health Outcomes - Linda Haddad; Debra Lynch Kelly; Linda S. Weglicki; Tracey E. Barnett; Anastasiya V. Ferrell; Roula Ghadban (SAGE Publishing, 2016)
Background Waterpipe smoking (WPS) is a social custom common in many Middle Eastern, North African, and Asian countries and has become increasingly popular in the US, especially among youth; however, WPS smoking may be increasing in the US adult population as well. There is a common belief among waterpipe (WP) smokers that WPS is less harmful than smoking cigarettes. Thus, this review aims to systematically explore the literature on the effects of WP tobacco smoking with a particular focus on cardiovascular and respiratory health outcomes as well as on oxidative stress, immunity, and cell cycle interference health outcomes. Methodology We conducted a systematic review, guided by the criteria of The Preferred Reporting Items for Systematic Reviews and Meta-Analyses, using the following online databases MEDLINE, CINAHL, ScienceDirect, PMC, and Cochrane Library. Results were summarized qualitatively. Results Forty studies met the inclusion criteria established for this review. Based on the existing evidence, several cardiovascular and respiratory physiologic health indicators and conditions have been shown to be negatively affected by WPS. In addition to the effects of nicotine and chemical toxicant exposures, WPS was significantly associated with an increase in heart rate, blood pressure, and lower pulmonary function test results, as well as a number of health conditions such as lung cancer, alterations in oxidative stress, immunity, and cell cycle interference. Conclusion The current literature provides evidence that WPS is associated with a number of negative health indicators and outcomes. There is need for more research related to WPS and its effects on health so that appropriate campaigns and prevention interventions can be implemented to control the epidemic increase of WPS in the US.